Pelaksanaan Collaborative Governance Dalam Pengembangan Kelompok Ekonomi Kreatif - Yuliani, Dini; Nursetiawan, Irfan; Taufiq, Otong Husni; Sujai, Ii (Journal of Management Review, 2023)
This study investigates the role and implementation of collaborative governance in the development of creative economy groups in rural areas. Collaboration between various parties including government, the private sector, and civil society is considered an important foundation in accelerating the growth and sustainability of the creative economy sector. This research will carry out an in-depth analysis of the structure and dynamics of collaboration between parties involved in the process of developing creative economy groups. The methodology of this study includes surveys, interviews, and documentation analysis to obtain a holistic understanding of how collaborative governance is applied in decision-making, strategic planning, and program implementation in the development of creative economy groups. Apart from that, supporting factors and obstacles that influence the effectiveness of collaborative governance in this context will also be considered. It is hoped that the results of this study will provide in-depth insight into the best strategies for optimizing collaborative governance in supporting the growth of creative economy groups. It is hoped that the implications of these findings can become the basis for more effective policies and practices in supporting the development of the creative economy sector at the local, regional, and national levels.